Developing a Sustainable Financial Model in Higher Education for Open Educational Resources - David Annand (Athabasca University Press, 2015)
Financial issues regarding the sustainable production, dissemination, and use of Open Educational Resources (OER) in higher education are reviewed and proposed solutions critiqued. Use of OER produce demonstrable cost savings for students. Yet OER development continues to rely almost completely on government and philanthropic funding. This indicates that a mismatch exists between the financial interests of students and those of higher education institutions. Before OER will be broadly adopted, changes to government policy are required to align institutional objectives with faculty motivations and student needs.